Synthesis, biological evaluation and docking studies of aurone derivatives on Xanthine oxidase enzyme - Rullah, Kamal; Khye, Saw Phin; Ang, Serene; Mohd Aluwi, Mohd Fadhlizil Fasihi; Lam, Kok Wai (UKM Press, 2018)
Inhibition of xanthine oxidase (XO) activity is an effective therapeutic approach for the treatment of diseases such as gout and hyperuricemia. Additionally, the use of XO inhibitors can further be extended to injury treatments such as ischemic reperfusion in various organs such as heart, liver and kidney. In this study, 7 aurone compounds were synthesized and tested on XO and compared with the positive control allopurinol. Compound 5e was identified as the most potent compound and was able to inhibit half of XO activity at 33.23 μM followed by compounds 5f and 5d at 210.22 μM and 302.0 μM, respectively. Finally, molecular docking study was conducted to understand the important binding interactions of the selected aurone with the active site of XO.